Comparison of prescribing criteria in hospitalised Australian elderly - Pattanaworasate W; Emmerton L; Pulver L; Winckel K (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
The Beers criteria (2003) and McLeod criteria (1997) have been applied internationally to quantify inappropriate prescribing in elderly populations. Similarly, guidelines have been published locally by the National Prescribing Service (NPS). Objective: This study aimed to adapt, evaluate and compare the utility of these three established criteria in measuring prescribing appropriateness in a sample of hospitalised elderly patients. Methods: Initial refinement of the criteria produced versions applicable to Australian practice. Inpatient records of 202 patients aged 65 years or older in six wards of the Princess Alexandra Hospital, Brisbane, Australia, were reviewed using the adapted criteria. 'Potentially inappropriate' prescribing was descriptively analysed using relevant denominators.Results: The adapted criteria collectively listed 70 'potentially inappropriate' medicines or drug groups and 116 'potentially inappropriate' prescribing practices. Patients (mean age 80.0; SD=8.3 years) were prescribed, a median of eight medicines (SD=4.0). At least one 'potentially inappropriate' medicine was identified in 110 (55%) patients. 'Potentially inappropriate' prescribing practices averaged 1.1 per patient (range 1-6). The adapted Beers criteria identified more 'potentially inappropriate' medicines/practices (44%, 101/232) than the McLeod criteria (41%) and NPS criteria (16%). Aspirin, benzodiazepines, beta-blockers and dipyridamole were most commonly identified.Conclusion: The Beers and McLeod criteria, developed internationally, required considerable modification for local prescribing. The three criteria differed in their focus and approaches, such that development and validation of national criteria, using the key features of these models, is recommended. There is potential to apply validated guidelines in clinical practice and review of prescribing, but only to supplement clinical judgement.